Semantically Augmented Exploitation of Pervasive Environments by Intelligent Agents - Amato, A.; Di Martino, B.; Venticinque, S. (2012 IEEE 10th International Symposium on Parallel and Distributed Processing with Applications, 2012)
Mobile devices can be used to improve the exploitation of reality by the user in pervasive environments. In this paper we present a software framework for augmenting the user's perception of reality by innovative applications and services. Mobile applications enable handheld devices to get information from pervasive sensors, as their own perceptors, in order to let the users benefit of context awareness. Furthermore they exploit information from the field to improve delivery of ubiquitous services and presentation of multimedia contents. We implemented tools to support experts in the domain of the Cultural Heritage to augment the archaeological site with these kind of services. Besides we developed a tourist guide that supports user's visit and enhances his cultural experience by an intelligent discovering and delivery of those information, which are relevant to the user's profile and to the environment conditions. In our approach software agents adapt themselves in response to a changing environment and are able to respond differently, creating entirely new plans, and thus changing their own behavior depending on their perceptions.